Czerniak błony naczyniowej u chorych z oczną lub oczno-skórną melanocytozą - Szuścik, Iwona; Romanowska-Dixon, Bożena; Jakubowska, Barbara; Orłowska-Heitzman, Jolanta (Klinika Oczna / Acta Ophthalmologica Polonica, 2008)
Purpose: To describe patients with ocular or oculodermal melanocytosis and uveal melanoma. Material and methods: In Departament of Ophthalmology in Krakow 4 patients with ocular and 1 with oculodermal melanocytosis and uveal melanoma were diagnosed. Results: In 4 patients with ocular melanocytosis and 1 with oculodermal melanocytosis the uveal melanoma was recognized and treated. Brachytherapy was used in 3 person, transcleral tumour resection in one case and in one enucleation was performed. During follow–up in two patients metastases to the liver were found. Conclusions: Patients with ocular and oculodermal melanocytosis should be regularly controled ophthalmoscopically for the occurrence of uveal melanoma.